Beyond Netflix and Amazon: MUBI and the curation of on-demand film. Issue 1 (2nd January 2019) - Smits, Roderik; Nikdel, E. W.
ABSTRACT: Whilst operating in the shadows of powerful market leaders Netflix and Amazon, the specialised subscription Video-on-Demand (VOD) platform MUBI has branded itself as a pioneering and innovative platform with a global presence in international markets. MUBI has put itself at the forefront of the evolving online market for specialised films after a period of trial and error. In particular, their business model has undergone radical change over the course of their brief history. We chart the historical development of MUBI with the purpose of analysing its business model and its role as cultural gatekeeper and tastemaker. Through a discussion of their engagement with online distribution, it becomes clear that MUBI's platform strategies are rooted in an underlying practice and philosophy that closely aligns with conventional traditions and practices of linear and physical media delivery formats. Therefore, we argue that established practices in the physical media market have been relocated online in somewhat new and interesting ways. We also scrutinise MUBI's response to the challenge of promoting specialised film in a crowded and volatile market. In particular, we analyse MUBI's recent venture into the wider business of distribution and demonstrate that this strategy is needed to add promotional values to their platform.